Technology Entrepreneurship Project (ENT 600) : Puma / Muhammad Akmal Rosli - Rosli, Muhammad Akmal (2021)
As a student in UiTM Perlis, it is a part of a study for everyone to undergo a case study project and take ENT600 course. So, for this purpose, I got the chance to research a corporate entity that manufactures a product that attract us, which is Puma, a sports good supplier and retailer. First, the general information regarding the corporate has been collected. Information is gathered through the primary and secondary source. In the second part of the report contains the specialized subject studies. The objective of the project is to figure on the background which is company information, background information and background history, organizational structure, products, and services that Puma provides. In this case study, I have analyzed the strength, weaknesses, opportunities, and threats of this company in the real business world by using SWOT analysis. Next, I studied regarding the product manufactured by Puma, which is primarily a technology utilized by the company for its selected product that we have chosen which is their running shoes. Here, I will explain the problems of the shoes that have grab my attention. The problem of the shoe I discovered is the shoes are stiffness which makes difficulties for runners. Next, is the shoe with high arch which is not suitable for runners. And lastly, the less brand value shoes developed by Puma has made it difficult for those who have wide feet to wear it. In this study, I will be explaining deeper regarding the problems and I would also be discussing the alternatives solutions towards the problems.